2015
DOI: 10.1002/rnj.171
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Reported Infection and Lymphedema Symptoms among Individuals with Extremity Lymphedema

Abstract: Select factors of income, self-care status, and site of lymphedema were associated with increased occurrence of infection and symptoms among individuals with extremity lymphedema. Longitudinal studies are needed to identify risk factors contributing to infections and symptoms in individuals with lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
1
12
1
3
Order By: Relevance
“…Salani et al identified that women undergoing surgery for endometrial cancer reported tightness, heaviness, and pain/ tenderness as the most commonly experienced symptoms on their lymphedema-affected legs [25]. Similar findings were reported in a recent publication; that is, individuals with arm or leg lymphedema frequently reported heaviness and numbness as their major symptoms [26,27]. Our findings were also congruent with recent reports of head and neck lymphedema [11,13].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Salani et al identified that women undergoing surgery for endometrial cancer reported tightness, heaviness, and pain/ tenderness as the most commonly experienced symptoms on their lymphedema-affected legs [25]. Similar findings were reported in a recent publication; that is, individuals with arm or leg lymphedema frequently reported heaviness and numbness as their major symptoms [26,27]. Our findings were also congruent with recent reports of head and neck lymphedema [11,13].…”
Section: Discussionsupporting
confidence: 94%
“…Second, individuals with head and neck lymphedema in the matched pair group reported more frequent and severe spontaneous pain involving the musculoskeletal system and skin. Pain has been reported in individuals with arm or leg lymphedema [25][26][27], but with much less frequency and severity [28]. Thus, this was an important finding.…”
Section: Discussionmentioning
confidence: 83%
“…3 Arbeiten (7 %) betrachteten sekundäre Lymphödeme bei nichtgynäkologischen Erkrankungen (Kopf-Hals-Karzinom, Melanom, Lymphangioleiomyomatose). 2 Arbeiten beschäftigten sich mit Infektionen als Folgeerkrankung des Lymphödems, 1 Arbeit mit Krankheitsfolgen von primären Lymphödemen [44][45][46][47][48][49].…”
Section: Hintergrundunclassified
“…Bei Kopf-und Halstumoren konnten lediglich therapiebezogene Faktoren, nicht jedoch Komorbiditäten, als Risikofaktoren für innere oder äußere Lymphödeme identifiziert werden [45].…”
Section: Hintergrundunclassified
“…This can result in physical discomfort, psychological distress, functional disability, cosmetic defect and chronic recurrent erysipelas 5. Affected arms are often stiff and prone to infections, which often require hospitalisation for antibiotics,6 or even surgery,7 a significant source of expenditure and hardship for many patients. To prevent deterioration from the swelling, patients are repeatedly obliged to wear uncomfortable elastic compression stockings, which serve as a continuous reminder of their cancerous status, increasing their anxiety and reducing their quality of life 8.…”
Section: Introductionmentioning
confidence: 99%